Revitalization of the Workforce Training System in Response to the Dynamics of Globalization: A Systematic Literature Review - Utami, Dian Sri; Prakosa, Hilman; Lataruva, Eisha; Hidayati, Retno (Research Horizon, 2024)
The global landscape of workforce training has been profoundly influenced by the forces of globalization, digital transformation, and the rapid evolution of job requirements. This paper presents a systematic literature review on the transformation of workforce training in the face of globalization's challenges and opportunities. By examining a wide range of scholarly sources, this study aims to identify emerging trends, prevailing challenges, and potential frameworks for effective workforce development. Findings indicate a growing emphasis on digital skills, adaptability, and lifelong learning, alongside the need for a comprehensive approach that addresses disparities in training accessibility. This review contributes insights into the critical elements for developing workforce training strategies that are globally competitive, inclusive, and resilient.